Properties of Modified Asphalt Concrete with Polyethene Terephthalate (Pet) as Additional Material - Kawi, Fikri; Wan Jusoh, Wan Amizah; Syed Zin, Syed Mohd Fareed (Progress in Engineering Application and Technology, 2025)
Plastic waste, particularly polyethylene terephthalate (PET), has become a significant environmental issue due to its extensive use and persistence in nature. The accumulation of PET waste in landfills and oceans poses a serious threat to the environment. To address this issue, the potential application of PET in asphalt mixtures for road construction was explored in this study. The research aimed to evaluate the effects of incorporating PET plastic waste into asphalt mixtures, focusing on the improvement of physical and mechanical properties. This study involved modifying asphalt concrete by adding different sizes of plastic waste (PET) using dry mixing methods. The properties of the modified asphalt binders were evaluated through testing, including penetration test and softening test, while the performance of the asphalt mixtures was assessed through Marshall stability and flow tests. The results indicated that the incorporation of PET into asphalt mixtures improved the high-temperature performance, showing enhanced resistance to rutting and cracking. The PET-modified asphalt also exhibited better elasticity and stability compared to conventional asphalt, especially under extreme temperature conditions. The findings suggest that PET-modified asphalt could be a viable solution for sustainable road construction, offering a dual benefit of reducing plastic waste and enhancing the performance of road materials. In conclusion, the study demonstrated that PET plastic waste can be effectively utilized in asphalt mixtures, contributing to more sustainable road construction practices. The use of PET in asphalt has the potential to improve the durability of road surfaces while addressing the global plastic waste crisis.